Cell‐based maximum entropy approximants for three‐dimensional domains: Application in large strain elastodynamics using the meshless total Lagrangian explicit dynamics method. (23rd October 2019) - Mountris, Konstantinos A.; Bourantas, George C.; Millán, Daniel; Joldes, Grand R.; Miller, Karol; Pueyo, Esther; Wittek, Adam
Summary: We present the cell‐based maximum entropy (CME) approximants in E 3 space by constructing the smooth approximation distance function to polyhedral surfaces. CME is a meshfree approximation method combining the properties of the maximum entropy approximants and the compact support of element‐based interpolants. The method is evaluated in problems of large strain elastodynamics for three‐dimensional (3D) continua using the well‐established meshless total Lagrangian explicit dynamics method. The accuracy and efficiency of the method is assessed in several numerical examples in terms of computational time, accuracy in boundary conditions imposition, and strain energy density error. Due to the smoothness of CME basis functions, the numerical stability in explicit time integration is preserved for large time step. The challenging task of essential boundary condition (EBC) imposition in noninterpolating meshless methods (eg, moving least squares) is eliminated in CME due to the weak Kronecker‐delta property. The EBCs are imposed directly, similar to the finite element method. CME is proven a valuable alternative to other meshless and element‐based methods for large‐scale elastodynamics in 3D. A naive implementation of the CME approximants in E 3 is available to download at https://www.mountris.org/software/mlab/cme .